Causal relationship between immune cells and prostate cancer: a Mendelian randomization study - Ye, Zhipeng; Deng, Xinpei; Zhang, Jinhui; Shao, Ruonan; Song, Cailu; Zhao, Jianfu; Tang, Hailin (Frontiers in Cell and Developmental Biology, 2024)
Despite the abundance of research indicating the participation of immune cells in prostate cancer development, establishing a definitive cause-and-effect relationship has proven to be a difficult undertaking. This study employs Mendelian randomization, leveraging genetic variables related to immune cells from publicly available genome-wide association studies (GWAS), to investigate this association. The primary analytical method used in this study is inverse variance weighting (IVW) analysis. Comprehensive sensitivity analyses were conducted to assess the heterogeneity and horizontal pleiotropy of the results. The study identifies four immune cell traits as causally contributing to prostate cancer risk, including CD127 -CD8 + T cell %CD8 + T cell (OR=1.0042, 95%CI:1.0011-1.0073, P=0.0077), CD45RA on CD39 + resting CD4 regulatory T cell (OR=1.0029, 95%CI:1.0008-1.0050, P=0.0065), CD62L -Dendritic Cell Absolute Count (OR=1.0016; 95%CI:1.0005-1.0026; P=0.0039), CX3CR1 on CD14 + CD16 -monocyte (OR=1.0024, 95%CI:1.0007-1.0040, P=0.0060). Additionally, two immune cell traits are identified as causally protective factors: CD4 on monocyte (OR=0.9975, 95%CI:0.9958-0.9992, P=0.0047), FSC-A on plasmacytoid Dendritic Cell (OR=0.9983, 95%CI:0.9970-0.9995, P=0.0070). Sensitivity analyses indicated no horizontal pleiotropy. Our MR study provide evidence for a causal relationship between immune cells and prostate cancer, holding implications for clinical diagnosis and treatment.Prostate cancer is a prevalent malignant tumor in elderly men, ranking as the most common solid malignancy in men in western countries, with an increasing incidence year by year (Rebello et al., 2021). Current research indicates that the occurrence of prostate cancer is primarily associated with factors such as age, hormones, race, and genetics (Bergengren et al., 2023). However, its etiology and pathogenesis are not fully understood. Treatment for prostate cancer primarily includes surgery, radiation therapy, and androgen deprivation therapy (Cha et al., 2020). Emerging treatment modalities have provided patients with a greater range of options. For example, the use of nanomaterials in conjunction with circRNA enhance the sensitivity of tumor cells to treatment